Effect of Mechanical Ventilation Mode Type on Intra- and Postoperative Blood Loss in Patients Undergoing Posterior Lumbar Interbody Fusion Surgery: A Randomized Controlled Trial. (July 2016) - Kang, Woon-Seok; Oh, Chung-Sik; Kwon, Won-Kyoung; Rhee, Ka Young; Lee, Yun Gu; Kim, Tae-Hoon; Lee, Suk Ha; Kim, Seong-Hyop
Abstract : Background: The aim of study was to evaluate the effect of mechanical ventilation mode type, pressure-controlled ventilation (PCV), or volume-controlled ventilation (VCV) on intra- and postoperative surgical bleeding in patients undergoing posterior lumbar interbody fusion (PLIF) surgery. Methods: This was a prospective, randomized, single-blinded, and parallel study that included 56 patients undergoing PLIF and who were mechanically ventilated using PCV or VCV. A permuted block randomization was used with a computer-generated list. The hemodynamic and respiratory parameters were measured after anesthesia induction in supine position, 5 min after patients were changed from supine to prone position, at the time of skin closure, and 5 min after the patients were changed from prone to supine position. The amount of intraoperative surgical bleeding, fluid administration, urine output, and transfusion requirement were measured at the end of surgery. The amount of postoperative bleeding and transfusion requirement were recorded every 24 h for 72 h. Results: The primary outcome was the amount of intraoperative surgical bleeding, and 56 patients were analyzed. The amount of intraoperative surgical bleeding was significantly less in the PCV group than that in the VCV group (median, 253.0 [interquartile range, 179.0 to 316.5] ml in PCV group vs. 382.5 [328.0 to 489.5] ml in VCV group; P < 0.001). Comparing other parameters between groups, only peak inspiratory pressure at each measurement point in PCV group was significantly lower than that in VCV group. No harmful events were recorded. Conclusion: Intraoperative PCV decreased intraoperative surgical bleeding in patients undergoing PLIF, which may be related to lower intraoperative peak inspiratory pressure. Abstract : Fifty-six patients having spine surgery were randomized. Intraoperative blood loss was 130 ml less with pressure- than with volume-controlled ventilation.